Anterior tonsillar pillar perforation during Glide Scope® video laryngoscope guided-intubation in an intubation patient with expected difficulty: a case report - Pin-on, Pathomporn; Lapisatepun, Worawut (Biomedical Sciences and Clinical Medicine, 2024)
There are several devices currently used to improve glottic view in patients with difficult intubation. The GlideScope® video laryngoscope is a fixed 60° angle laryngoscope blade, with embedded high-resolution camera and separate monitor screen. It is an optional method, especially for difficult intubation, as it improves the epiglottic tip and vocal cord visualization (Cormack and Lehane grade 3 and 4). GlideScope® application and intubation even provides the potential advantage of a certain step that is extremely important in avoiding oral cavity and oropharyngeal injuries. This report describes a case of anterior tonsillar perforation, which was detected immediately during endotracheal intubation guided by GlideScope®.